Menjaga Profesionalisme : Etika dalam Asesmen Psikologi pada Layanan Bimbingan dan Konseling (International Forum of Researchers and Lecturers, 2025)
This article discusses the important role of guidance and counseling in supporting the development of students through ethical and professional psychological assessments. Guidance and counseling aim to help individuals develop their potential, overcome problems, and improve their quality of life. Psychological assessment becomes a crucial component in this process, requiring attention to ethical aspects, confidentiality, and the competence of the counselor. The use of psychological tests must adhere to the ethical codes established by professional associations, such as ABKIN and HIMPSI, to ensure that counselors possess adequate skills in using assessment instruments. This article also identifies challenges in maintaining objectivity in assessments, such as subjective bias and environmental pressure, and offers effective solutions, including professional training and team collaboration. By applying ethical principles and competencies, guidance and counseling can provide quality services, protect the rights and welfare of students, and contribute to the development of individuals and society as a whole.